2020
DOI: 10.1080/1331677x.2020.1756373
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and consequences of word of mouth communication from the senders’ and receivers’ perspectives: the evidence from the Croatian adult population

Abstract: This article addresses the issue of predicting and stimulating consumers' word of mouth communication (WOM). It contributes to the WOM literature by examining and comparing the magnitude of effects of a set of antecedents and consequences of WOM information spread and WOM information seek in one model. The data collected from consumer survey in Croatia were analysed using structural equation modelling (SEM). The results reveal that consumer innovativeness, followed by price sensitivity and attitudes towards ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…Consumer BIN had a positive and significant effect on consumer BAB, so actual BAB may be consistent with their pre-BIN. Accordingly, pre-banking intention was a direct antecedent of consumer actual BAB, corroborating previous studies (Milaković et al. , 2020; Mahmood and Baharun, 2018).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Consumer BIN had a positive and significant effect on consumer BAB, so actual BAB may be consistent with their pre-BIN. Accordingly, pre-banking intention was a direct antecedent of consumer actual BAB, corroborating previous studies (Milaković et al. , 2020; Mahmood and Baharun, 2018).…”
Section: Resultssupporting
confidence: 90%
“…Consumer BIN had a positive and significant effect on consumer BAB, so actual BAB may be consistent with their pre-BIN. Accordingly, pre-banking intention was a direct antecedent of consumer actual BAB, corroborating previous studies (Milakovi c et al, 2020;Mahmood and Baharun, 2018). Thus, this study presents a noteworthy theoretical contribution, particularly in the financial service sector, in that it has narrowed the theoretical gaps in former research (Bullock et al, 2020;Lazaroiu et al, 2020;Lin et al, 2020) by extending the TPB to account for the emotional and habitual antecedents that affect pre-purchase decisions and their synergistic effect.…”
Section: Ghanaian Consumer Pre-banking Behavioursupporting
confidence: 85%
See 2 more Smart Citations
“…A survey showed that 83% of consumers agree that eWOM affects their final decisions (Channel Advisor, 2011). eWOM communication was suggested to be a more efficient communication channel with less investments than traditional advertising (Milakovi c et al, 2020) and has been recognized as a process of personal influence that affects consumers' attitudes, decision-making, and purchases (Ansary & Hashim, 2018;Lee & Choeh, 2018;Bucko & Kakalej c ık, 2018). Kim et al (2019) believe that eWOM volume have a very important impact on DVD sales.…”
mentioning
confidence: 99%